Modeling the implications of internal audit effectiveness on value for money and sustainable procurement performance: An application of structural equation modeling - Appiah Michael Karikari; Paul Kwaku Tettevi; Newman Amaning; Emmanuel Opoku Ware; Charles Kwarteng (Cogent Business & Management, 2022)
The Government of Ghana spends approximately seventy percent of its annual budget on the procurement of goods, services, and public works. The Public Procurement Acts (Act 663, and Act, 914) were established to regulate public procurement activities and ensure transparency, accountability, and Value for Money (VFM) in the procurement processes. Contrariwise, the extent of misappropriations of public funds in Ghana by public officials has reached an all-time high. To address this concern, our paper is aimed to develop a model to explain the extent to which Internal Audit Effectiveness (IAE) drives VFM, and Sustainable Public Procurement (SPP). This paper is a cross-sectional survey-based study involving public agencies in Ghana. The population of the study comprised 72 District Assemblies across the Greater Accra and Ashanti regions. Stratified sampling technique has been used to randomly select 200 participants comprising internal auditors, procurement officers, accountants, and finance officers for the study. Smart-PLS software and the Structural Equation Modelling (SEM) approach have been used to analyze the survey data, and test the hypotheses of the study. The study has revealed that internal audit competency, internal audit independence, external auditors' role, and top management support are the main determinants of IAE. Again, our mediation analysis has revealed that IAE drives both VFM and SPP. The results have further shown that an increase in VFM positively affects SPP. These results have implications for the reinforcement of internal audit agency regulations of 2003 (Act 658) and public procurement act 2003 (Act 663) and the amended Act 2016 (Act 914). Again, the results have extended exciting knowledge on the IAE by linking it up with SPP and VFM in a developing country context where such studies still remain fuzzy.
Keywords: 650; internal audit effectiveness; structural equation modeling; sustainable procurement; value for money